Introducing an esthetic treatment of malocclusion: Ultrasound‐assisted augmentation of premaxilla with injectable hyaluronic acid filler - Pantea Shekarriz; Pardis Shojaee (Clinical Case Reports, 2023)
Abstract With advances in the ultrasound‐assisted esthetic procedures, filler injection can successfully be used for cosmetic correction of face structural imperfections. Here, we present a new filler injection method by targeting two anatomic landmarks which effectively improved the appearance of a mandibular prognathism case who was a maxillofacial cosmetic surgery candidate.